Effect of methoxatin loaded chitosan conduit on deep digital flexor tendon healing in rabbits: An animal model study - Negin Mozafari; Mohammad Velayati; Azad Bahrampour; Erfan Yarahmadi; Roghaiyeh Neisari; Rahim Mohammadi (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2020)
Chitosan is of great interest in regenerative medicine because of its plentiful properties, like biocompatibility, biodegradability and non-toxicity. The objective of the present study was histopathological and biomechanical survey on effect of methoxatin loaded chitosan conduit on Deep Digital Flexor Tendon (DDFT) healing in rabbit models. Eighteen healthy male white New Zealand rabbits were randomized into three groups of six animals each. In CONTROL group the DDF tenotomy was performed and the sumps were sutured. In CTN (chitosan) group the DDF tenotomy was performed and the sumps were sutured and CTN conduit was wrapped around the damaged area. In CTN/METHO (chitosan/methoxatin) group the procedure was the same as CTN group as well as local administration of 100 µL methoxatin (100 µg/Rabbit) into the CTN conduit. The histopathological assessments including inflammation, angiogenesis and collagen fibers arrangement, and biomechanical assessments were performed after 8 weeks. Histopathological observations showed that the conduit was absorbed and adhesion around the tendon was deceased in CTN and CTN/METHO groups. There were no noticeable signs of infection and tissue reaction in the granulation tissue in CTN/METHO group compared to other groups (P<0.05). Local administration of methoxatin in combination with chitosan conduit could accelerate deep digital flexor tendon healing via decrease in adhesion around the tendon with no signs of excessive tissue reaction or infection in rabbits.